Infestation of crop fields by Striga species in the savanna zones of northeast Nigeria - Dugje, I.Y.; Kamara, A.; Omoigui, L.O. (Elsevier, 2006)
Parasitism of crop plants by Striga species is a major constraint in the savanna zones of West Africa. Farmers ranked Striga as a leading constraint during a livelihood analysis of 30 communities in northeast Nigeria. A field survey was conducted to ascertain the extent of infestation by Striga spp. About 935 crop and fallow fields were surveyed across 30 communities in three agro-ecological zones. Four major Striga species were identified: Striga hermonthica in sorghum or maize; Striga aspera in rice; Striga densiflora in pearl millet and fallow and Striga gesnerioides in cowpea. About 68% of all fields sampled were infested, about 75% of compound fields and 60% of bush fields. The level of infestation was 60% in southern Guinea, 68% in Sudan and 74% in northern Guinea savanna. The level of infestation of cereal fields by S. hermonthica was in the order of Sudan savanna > Northern Guinea > Southern Guinea. Infestation of cowpea with S. gesnerioides was in the order of Northern Guinea savanna > Sudan savanna > Southern Guinea savanna. Across the three ecozones, about 85% of fields planted to maize and sorghum were infested with S. hermonthica and 81% of cowpea fields with S. gesenerioides. S. aspera infested 40–59% of rice fields and S. densiflora infested 27–60% of millet fields and fallow.